2002
DOI: 10.2134/jeq2002.0846
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Comparison of Landscape Pattern–Normalized Difference Vegetation Index (NDVI) Relationships to Central Plains Stream Conditions

Abstract: We explored relationships of water quality parameters with landscape pattern metrics (LPMs), land use-land cover (LULC) proportions, and the advanced very high resolution radiometer (AVHRR) normalized difference vegetation index (NDVI) or NDVI-derived metrics. Stream sites (271) in Nebraska, Kansas, and Missouri were sampled for water quality parameters, the index of biotic integrity, and a habitat index in either 1994 or 1995. Although a combination of LPMs (interspersion and juxtaposition index, patch densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Correlation analysis showed that first axis of DCA and conductivity was strongly correlated in both the ecotypes ( p < 0.05). This supports the assumption that such axis represents the main gradient of eutrophication, since conductivity is generally an adequate water quality variable expressing nutrient concentration (Webb and Walling, 1996;Ladson et al, 1999;Griffith et al, 2002). Therefore, we can apply the proposed methodology that fits the species scores along this axis according to the logit model.…”
Section: Resultssupporting
confidence: 75%
“…Correlation analysis showed that first axis of DCA and conductivity was strongly correlated in both the ecotypes ( p < 0.05). This supports the assumption that such axis represents the main gradient of eutrophication, since conductivity is generally an adequate water quality variable expressing nutrient concentration (Webb and Walling, 1996;Ladson et al, 1999;Griffith et al, 2002). Therefore, we can apply the proposed methodology that fits the species scores along this axis according to the logit model.…”
Section: Resultssupporting
confidence: 75%
“…(Ritter, 1986;Battaglin and Goolsby, 1997;McFarland and Hauck, 1999;Arheimer and Liden, 2000;Liu et al, 2000;Ometo et al, 2000;Sliva and Williams, 2001;Smith et al, 2001;Donner, 2003;Meador and Goldstein, 2003;Santos-Roman et al, 2003;Turner and Rabalais, 2003;Carle et al, 2005;Xian et al, 2007;Zampella et al, 2007;Chang, 2008;Coats et al, 2008;Amiri and Nakane, 2009;Atkinson et al, 2009). Understandings of such empirical relationships can help assess conditions of unmonitored water bodies, identify human activities that significantly contribute to pollution as well as critical areas that are at risk, and promote management practices to reduce nonpoint source pollution (McFarland and Hauck, 1999;Gergel et al, 2002;Griffith et al, 2002;Baker, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 25% of its minimize the effects of shadows caused by topography (VOROVENCII, 2014). Although NDVI is sensitive to soil and atmospheric effects, it is a good indicator of the total amount of vegetation (HENEBRY, 1993) and is considered important for the analysis of land cover structure and temporal changes (GRIFFITH et al, 2002;SADER, 2003).…”
Section: Study Areamentioning
confidence: 99%
“…Several works have investigated environmental changes, using spatial heterogeneity derived from various types of remote sensing data (WU et al, 2000;HENEBRY, 2009 In some studies, the Normalized Difference Vegetation Index (NDVI) has been used to detect and analyse spatial heterogeneity using semivariograms (GARRIGUES et al, 2006;BALAGUER-BESER et al, 2013). NDVI, which represents an especially informative vector for landscape structure and temporal change analyses (GRIFFITH et al, 2002), has been used in numerous studies of vegetation dynamics because of its simplicity and close relationship to variables of ecological interest such as land cover change and disturbance propagation at multiple scales (ZURLINI et al, 2006;ZACCARELLI et al, 2008).…”
Section: Introductionmentioning
confidence: 99%